Assessment of Surrogate of Ecosystem Health Using Indicator Species and Mixed-Species Bird Flock: DOI: 10.32526/ennrj.17.3.2019.18 - L. Winarni, Nurul; Nuruliawati, Nuruliawati; Afifah, Zahrah (Environment and Natural Resources Journal, 2019)
Investigation of the use of indicator species as a surrogate for ecosystem health was conducted during 2014 in the periphery of the Bukit Barisan Selatan National Park, Lampung, Indonesia. The survey area composed of forest, edge, and agricultural areas in three sites at the Pemerihan village. We used point count for bird surveys within 1 km transect to obtain the data and ad-libitum observation for mixed-species bird flock. The analysis was made by using Indicator Value (IV) to select the potential indicator species which complemented how mixed-flock groups formed at the sites and further analyzed by using principal component analysis. Among 127 species recorded, one species has been identified with high IV (IV>60) and 15 species have intermediate IV (30<IV<60). Our results suggested that Sooty-headed Bulbuls Pycnonotus aurigaster are the species with the highest IV which are exploiter species and indicator for agricultural gardens. Moreover, none of the birds with highest IV overlap among habitats, which indicate that proportions are very specific in terms of habitat types. Based on principal component analysis, mixed-flocks tend to comprise of edge-to-forest species and formed at edge which may indicate food availability in the area.